2015
DOI: 10.1111/itor.12175
|View full text |Cite
|
Sign up to set email alerts
|

A simulation model of a coordinated decentralized supply chain

Abstract: This paper presents a simulation-based study of a coordinated, decentralized linear supply chain (SC) system. In the proposed model, any supply tier considers its successors as part of its inventory system and generates replenishment orders on the basis of its partners' operational information. We show that the proposed coordinated decision-making process creates a reduction in information distortion along an SC compared with a traditional, noncoordinated strategy. A novel result is that we show how a coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 115 publications
(149 reference statements)
0
17
0
Order By: Relevance
“…Unlike, (14) formalizes the APVIOBPCS policy adopted by echelons that benefit from up-to-date information on the order placed not only by the direct customer, but also by other downstream echelons. Equation (14) differs from (13) in the first component.…”
Section: Modelling Assuptions and Mathematical Formalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike, (14) formalizes the APVIOBPCS policy adopted by echelons that benefit from up-to-date information on the order placed not only by the direct customer, but also by other downstream echelons. Equation (14) differs from (13) in the first component.…”
Section: Modelling Assuptions and Mathematical Formalizationmentioning
confidence: 99%
“…Several authors have shown how SC collaboration and IS increase members' performance by limiting noxious phenomenon such as the costly bullwhip effect [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial for manufacturers to make the right decision on developing the right serial products with right function and performance. Meanwhile, as the product's core part plays a key role in the function and performance of the product, many manufacturers invite their core part suppliers to conduct collaborative R&D to make sure that the core part well matches all products of the same series [4]. It has become the key issue of a modern manufacturer building the competitive advantage that makes the collaborative R&D and pricing policy of the product according to customers' preference and selection behavior, in order to develop a series of products satisfying demands of heterogeneous customers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the information distortion will propagate through the supply chain, as seen in the bullwhip effect [6,7]. Inventory inaccuracy often results in the overall poor performance of the supply chain, especially when information asymmetry exists between the supplier and the retailer [8].…”
Section: Introductionmentioning
confidence: 99%